Bishop John Philip Saklil’s Theological Preference for The Indigenous Papuans: An Attempt to Respond to People's Doubts - Kira, Alfonsus Biru; Barril, Dante Salces (Asosiasi Ahli Filsafat Keilahian Indonesia, 2023)
This research explores and answers the question: What is Bishop John Philip Saklil's contribution to developing the Indigenous Papuans of the Timika Diocese Catholic Church? The church’s workers will use the answer to the question in making pastoral programs in their parish and responding to the people’s doubts about the church’s ministry and its preference for indigenous Papuans. This research was also made to increase people’s awareness of the problems in Papua and how important it is for us to give priority to Indigenous Papuans. The method used in this study is an analysis of two books related to Bishop Saklil: